2007
DOI: 10.1183/09031936.00149206
|View full text |Cite
|
Sign up to set email alerts
|

First months of employment and new onset of rhinitis in adolescents

Abstract: The aim of the present study was to investigate the incidence of rhinitis in adolescents, taking into account the duration and type of employment in holiday and vocational jobs, and to study latency until development of symptoms.Participants of the International Study of Asthma and Allergies in Childhood (ISAAC)-II study in Munich and Dresden (Germany), who were enrolled in 1995, were re-contacted by a postal questionnaire in 2002 (aged 16-18 yrs). The questionnaire focused on allergic rhinitis, type and durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…A limitation of our study might be that even though participants were followed for ,12 years, they were still very young in SOLAR II and just at the beginning of their working lives. Many studies have shown that incidence of asthma and allergies may be highest in the first 6-12 months of a job [18,32,35], whereas our participants had indicated average job durations of 3 months, with a maximum of 21 months. Therefore, exposure times might have been too short to detect potential adverse health effects.…”
Section: Strengths and Limitationsmentioning
confidence: 56%
“…A limitation of our study might be that even though participants were followed for ,12 years, they were still very young in SOLAR II and just at the beginning of their working lives. Many studies have shown that incidence of asthma and allergies may be highest in the first 6-12 months of a job [18,32,35], whereas our participants had indicated average job durations of 3 months, with a maximum of 21 months. Therefore, exposure times might have been too short to detect potential adverse health effects.…”
Section: Strengths and Limitationsmentioning
confidence: 56%
“…The OR for physician-diagnosed rhinitis in the exposed group was 0.6. 17 A previous study of our group did not indicate an association between exposure to ICA, MIC, or formaldehyde and reduced lung function, but nasal symptoms were reported by significant numbers of both the exposed workers and the referents. 11 Because of these results, nasal examination was added in the cross-sectional study described in this article.…”
mentioning
confidence: 77%
“…Studies have shown that teenagers who work in high-risk occupational environments have at greater risk of developing new onset rhinitis than unemployed controls and that symptoms can develop within the first 9 months of starting work [50]. As such, secondary prevention strategies are important to help prevent the progression of symptoms in sensitized individuals.…”
Section: Prevention and Treatmentmentioning
confidence: 98%